2015
DOI: 10.1108/ijph-02-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Drug and alcohol use and treatment for Australian Indigenous and non-Indigenous prisoners: demand reduction strategies

Abstract: Very little is known about Indigenous specific drug and alcohol programs in Australian prisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This has been found both locally in Australia (see e.g. Dolan et al, 2015;Gilles et al, 2008) as well as a number of jurisdictions internationally (e.g. Binswanger et al, 2009;Singleton et al, 2003).…”
mentioning
confidence: 78%
“…This has been found both locally in Australia (see e.g. Dolan et al, 2015;Gilles et al, 2008) as well as a number of jurisdictions internationally (e.g. Binswanger et al, 2009;Singleton et al, 2003).…”
mentioning
confidence: 78%
“…It was concluded that prison provided an opportunity for treatment and rehabilitation, particularly for the Indigenous population, who were more likely to use health services in prison than in the community. 26 A separate study of cannabis withdrawal among Indigenous people in prison in Australia found that the majority of current cannabis users experienced withdrawal symptoms, indicating that this is common, but there was no standard treatment for managing cannabis withdrawal in prison. 27…”
Section: People In Custody Aboriginal People In Custodymentioning
confidence: 99%
“…Limited literature exists on the availability and effectiveness of alcohol-related interventions in prisons [14]. Prisoners, especially those who are Indigenous, often have limited engagement with health care while in the community [15,16]. Therefore, periods of incarceration, although unfortunate, often present an opportunity to intervene with, and offer treatment to, this vulnerable group.…”
Section: Introductionmentioning
confidence: 99%